Epidemiology of Zoonotic Hepatitis E: A Community-Based Surveillance Study in a Rural Population in China - Zhu, Feng-Cai (Public Library of Science, 2014)
BACKGROUND: Hepatitis E is caused by two viral genotype groups: human types and zoonotic types. Current understanding of the epidemiology of the zoonotic hepatitis E disease is founded largely on hospital-based studies. METHODS: The epidemiology of hepatitis E was investigated in a community-based surveillance study conducted over one year in a rural city in eastern China with a registered population of 400,162. RESULTS: The seroprevalence of hepatitis E in the cohort was 38%. The incidence of hepatitis E was 2.8/10,000 person-years. Totally 93.5% of the infections were attributed to genotype 4 and the rest, to genotype 1. Hepatitis E accounted for 28.4% (102/359) of the acute hepatitis cases and 68.9% (102/148) of the acute viral hepatitis cases in this area of China. The disease occurred sporadically with a higher prevalence during the cold season and in men, with the male-to-female ratio of 3∶1. Additionally, the incidence of hepatitis E increased with age. Hepatitis B virus carriers have an increased risk of contracting hepatitis E than the general population (OR = 2.5, 95%CI 1.5–4.2). Pre-existing immunity to hepatitis E lowered the risk (relative risk  = 0.34, 95% CI 0.21–0.55) and reduced the severity of the disease. CONCLUSIONS: Hepatitis E in the rural population of China is essentially that of a zoonosis due to the genotype 4 virus, the epidemiology of which is similar to that due to the other zoonotic genotype 3 virus.